Adopting Generative AI for Literature Reviews: An Epistemological Perspective - Schryen, Guido; Marrone, Mauricio; Yang, Jiaqi (Proceedings of the 57th Hawaii International Conference on System Science (HICSS 2024))

A Design Theory for Spontaneous Volunteer Coordination Systems in Disaster Response - Betke, Hans; Sperling, Martina; Schryen, Guido; Sackmann, Stefan (Proceedings of the 57th Hawaii International Conference on System Science (HICSS 2024))

Molecular-scale synchrotron X-ray investigations of solid-liquid interfaces in lithium-ion batteries - Cao, Chuntian; Steinrück, Hans-Georg (Reference Module in Chemistry, Molecular Sciences and Chemical Engineering)

Didaktik der Sozialpädagogik – Entwicklungslinien, Diskurse und Herausforderungen. - Göddertz, Nina (Zeitschrift für Pädagogikunterricht)

Freudig in die Schlacht - Emotionen als Codes für die recta intentio im gerechten Krieg (8.- 10. Jahrhundert) - Foerster, Anne (Emotionen im Krieg - Krieg der Emotionen)

The Swineherd’s Wife who Scolded the King - Foerster, Anne (Women in Early Medieval England)

Eadburh of Wessex - Foerster, Anne (Women in Early Medieval England)

Seaxburh - Foerster, Anne (Women in Early Medieval England)

Exploring Capabilities for the Smart Service Transformation in Manufacturing: Insights from Theory and Practice - Koldewey, Christian; Fichtler, Timm; Scholtysik, Michel; Biehler, Jan; Schreiner, Nick; Sommer, Franziska; Schacht, Maximilian; Kaufmann, Jonas; Rabe, Martin; Sedlmeier, Joachim; Dumitrescu, Roman
Digital Servitization is one of the significant trends affecting the manufacturing industry. Companies try to tackle challenges regarding their differentiation and profitability using digital services. One specific type of digital services are smart services, which are digital services built on data from smart products. Introducing these kinds of offerings into the portfolio of manufacturing companies is not trivial. Moreover, they require conscious action to align all relevant capabilities to realize the respective business goals. However, what capabilities are generally relevant for smart services remains opaque. We conducted a systematic literature review to identify them and extended the results through an interview study. Our analysis results in 78 capabilities clustered among 12 principles and six dimensions. These results provide significant support for the smart service transformation of manufacturing companies and for structuring the research field of smart services.
Keywords: Digital Servitization; Transformation; Capabilities; Maturity; Smart Services

Preface - Fuchs, Christian (Yuqi Na: The Chinese Internet. Political Economy and Digital Discourse)